An extracellular Leptospira interrogans leucine‐rich repeat protein binds human E‐ and VE‐cadherins. (26th September 2018) - Eshghi, Azad; Gaultney, Robert A.; England, Patrick; Brûlé, Sébastien; Miras, Isabelle; Sato, Hiromi; Coburn, Jenifer; Bellalou, Jacques; Moriarty, Tara J.; Haouz, Ahmed; Picardeau, Mathieu
Abstract: Pathogenic Leptospira bacteria are the causative agents of leptospirosis, a zoonotic disease affecting animals and humans worldwide. These pathogenic species have the ability to rapidly cross host tissue barriers by a yet unknown mechanism. A comparative analysis of pathogens and saprophytes revealed a higher abundance of genes encoding proteins with leucine‐rich repeat (LRR) domains in the genomes of pathogens. In other bacterial pathogens, proteins with LRR domains have been shown to be involved in mediating host cell attachment and invasion. One protein from the pathogenic species Leptospira interrogans, LIC10831, has been previously analysed via X‐ray crystallography, with findings suggesting it may be an important bacterial adhesin. Herein we show that LIC10831 elicits an antibody response in infected animals, is actively secreted by the bacterium, and binds human E‐ and VE‐cadherins. These results provide biochemical and cellular evidences of LRR protein‐mediated host–pathogen interactions and identify a new multireceptor binding protein from this infectious Leptospira species.